2011
DOI: 10.1107/s1600536811012566
|View full text |Cite
|
Sign up to set email alerts
|

Diaqua[5,5′-dicarboxy-2,2′-(propane-1,3-diyl)bis(1H-imidazole-4-carboxylato)]manganese(II)

Abstract: The complex mol­ecule of the title compound, [Mn(C13H10N4O8)(H2O)2] or [Mn(H4pbidc)(H2O)2] (H6pbidc = 2,2′-(propane-1,3-di­yl)bis­(1H-imidazole-4,5-dicarb­oxy­lic acid), has 2 symmetry with the twofold rotation axis running through the Mn2+ cation and the central C atom of the propanediyl unit. The cation is six-coordinated by two N atoms and two O atoms from one H4pbidc2− anion and two water O atoms in a considerably distorted octa­hedral coordination. In the crystal, adjacent mol­ecules are linked through O—… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…For example, [Ca(H 4 pbidc)(H 2 O) 3 ]·4H 2 O, [Ni(H 4 pbidc)(H 2 O) 2 ]·2H 2 O and [Mn(H 4 pbidc)(H 2 O) 2 ] are mononuclear complexes in which each tetradentate H 4 pbidc 2− anion only coordinate to one metal ion in N,O-chelating fashion. 1820 These results indicate that changing the metal ion can influence the coordination mode of H 4 pbidc 2− anion and thus influence the structures and properties of the resulting complexes. The BSA-binding properties of complex 1 were investigated by fluorescence measurements.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…For example, [Ca(H 4 pbidc)(H 2 O) 3 ]·4H 2 O, [Ni(H 4 pbidc)(H 2 O) 2 ]·2H 2 O and [Mn(H 4 pbidc)(H 2 O) 2 ] are mononuclear complexes in which each tetradentate H 4 pbidc 2− anion only coordinate to one metal ion in N,O-chelating fashion. 1820 These results indicate that changing the metal ion can influence the coordination mode of H 4 pbidc 2− anion and thus influence the structures and properties of the resulting complexes. The BSA-binding properties of complex 1 were investigated by fluorescence measurements.…”
Section: Discussionmentioning
confidence: 91%
“…Through investigation of the literature, we found that four complexes involving H 6 pbidc ligand, including [Mn(H 4 pbidc)(H 2 O) 2 ], 18 [Ni(H 4 pbidc)(H 2 O) 2 ]·2H 2 O, 19 [Ca(H 4 pbidc)(H 2 O) 3 ]·4H 2 O 20 , and [Co(H 4 pbidc)(pyridine)]·4,4′-bipyridine, 21 have been reported. In this work, a new complex [Cd(H 4 pbidc)(H 2 O)] n ( 1 ) with different compositions and architectures from those of the reported complexes can be obtained by using CdCl 2 ·2.5H 2 O and H 6 pbidc as starting materials.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations